Discriptive study to find out factors associated with teenage prgnancies at Mathugama MOH area from 01.01. 2006 to 31.12.2006 - Weerabaddana, Dissanayake, D. R (My University, 2007)
Sixty four adolescent mothers who had been registered with the PHM i year 2006 ( From 1st of January 2006 to 31st Dencember 2006) . Mean age of adolescent pregnant mothers was 17 yeard and 8 months ( SD =1) year and 4 months). More than one third of adolescent mothers had no schooling or had schooling within primary grades. Nearly 97 percent of adolescent mothers belong to lower social class . Usage of contraception to delay the first pregnancy was very low in both groups. But even after partus only 56 percent adolescent mothers use contraception. Popular method of post partum contraception was DMPA.